PEMBERDAYAAN KELOMPOK IBU PKK MELALUI PELATIHAN OLAHAN PANGAN LIDAH BUAYA DENGAN METODE PARTICIPATORY RURAL APPRAISAL - Nurhaida, D.; Busnetty, I.; Tambunan, T.T.H.; Munawar, M.A. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i04.p11, 2023)
This community service activity was given to a women’s group in RT 007 RW 13 Sukadanau Village, West Cikarang District, Bekasi, West Java. This activity aims to provide training and assistance in processing aloe vera into processed food products that have economic value. This activity is a collaboration between the Faculty of Economics and Business, Trisakti University, and PT. Coca-Cola Europacific Partners Indonesia, together with village officials and the local community. The methods used are "participatory rural appraisal" (PRA) and the transfer of knowledge, and technology. The results of the evaluation on the material provided, the transfer of knowledge and technology and the participation of the members were generally very good. The results obtained are in the form of: 1) cultivation of aloe vera plants, 2) processed food products from aloe vera, and 3) formation of home-based MSMEs. Keywords: Sukadanau village, PKK groups, aloe vera, empowerment